Information Systems Audit Using the 2019 COBIT Framework with Domain DSS01 and BAI04 on the Grand Landak Hotel Reservation System - Achmad, Fatih Nur; Pranata, Yolia Budi; Sembiring Milala, Efria Surya (IC-ITECHS, 2024)
Grand Landak Hotel is one of the hotels that has implemented information systems in their operations, one of which is the room booking or reservation section. At this time the reservation system is used by the front office of the hotel by the receptionist, which is part of the hotel's front office. Therefore the system must be able to manage, store and maintain data security and the system can operate when there is an increase in reservations. So this research aims to evaluate the operational efficiency and availability of the reservation system in the Front Office Department of the Grand Landak Hotel using the COBIT 2019 framework. This research focuses on two main domains, namely DSS01 (Managed Operations) and BAI04 (Managed Availability and Capacity). While the data was obtained through interviews with the general manager and front office staff of the hotel. The results showed that the service process has been running well with a result of 49.4 percent and for capacity of 54.8 percent but technological innovation requires more attention, especially in actively involving employees in the process of implementing new systems.